Digitalisasi Manajemen Pendidikan Islam untuk Mewujudkan Edupreneurship - DWIKI AL AKHYAR (ALBAHRU, 2023)
Digitalization of Islamic education is a concept that systematizes or develops human thinking through Islamic education by introducing the core Islamic values contained in the Al-Qur'an and Hadith. This concept is divided into two models, namely the reconstruction of role components in Islamic education and the synergy of educational institutions in Islamic education. The second model above focuses on digitizing Islamic education to support edupreneurship. Management of Islamic Education in realizing edupreneurship is a step in determining the climate and potential of edupreneurship in digitalization. This kind of educational management is needed by society to create and develop various creative and prosperous businesses, especially in vocational or vocational education. In this case, there are several aspects that need attention as an effort to realize edupreneurship management in digitalization, namely entrepreneurial learning.